IMPLEMENTASI ALGORITMA NEAREST NEIGHBOR PADA PENERIMAAN PEGAWAI BARU PADA MTS IKHWANUTS TSALITS TALUN KENAS - Sitepu, Rahmad Dani; Buulolo, Efori (STMIK Budi Darma, 2017)
Accumulation ofnemployeenacceptance file on unatapped MTs Ikhwanuts Tsalits Talun Kenas is a problem that must be solved well, in order to create a utilization of science in the process of receiving employess. In data mining, there are many branches of science contained one of which is nearest neighbor. Nearest neighbor is a method of data mning by calculating the proximity between new cases and old cases. Appropriate steps taken to utilize the science of data mining in overcoming the accumulation of existing files that is implementing the method nearest neighbor